Understanding Teacher Retention Challenges: A Quality Analysis of Human Resource Strategies - Juwarti, Juwarti; Octafian, Ray (PT. Riset Press International, 2025)
This research aimed to explore the factors influencing teacher retention at SMA Negeri 1 Tuntang, Kabupaten Semarang, focusing on the role of school leadership, job satisfaction, financial compensation, workload, and professional development. A qualitative case study approach was employed, utilizing interviews with teachers and school leaders to gather in-depth insights into the challenges and strategies related to teacher retention in a rural school setting. The findings revealed that school leadership plays a critical role in fostering a supportive environment for teachers, with leadership practices such as mentorship, professional development opportunities, and inclusive decision-making processes being key drivers of teacher retention. Additionally, job satisfaction, particularly in collegiality, administrative support, and work-life balance, was a significant factor in teachers' decisions to stay. While not the sole determinant, financial compensation was also identified as an important consideration, especially for teachers with long-term financial commitments. The research emphasizes the importance of a holistic approach to teacher retention, highlighting the need for comprehensive human resource strategies that consider both professional and personal factors. This study contributes original insights into teacher retention in rural Indonesian schools, offering practical recommendations for improving retention rates through enhanced leadership practices and support systems. The value of this research lies in its potential to inform policies and practices that can improve teacher retention, thereby enhancing the quality of education in rural areas.